(untitled) (Journal of Fiber Bioengineering and Informatics, 2009)
A scientific understanding on the reduction of breast displacements during activities will be necessary for the future development of optimal sports bras in order to prevent breast injury. This study aims to evaluate the shock absorbing performance of different sports bras, and to analyze the factors involved. Three healthy women were invited to participate in the experiments. They wore four types of sports bras of two different support levels and performed three different activities. Breast movements were recorded by a 6-camera Vicon motion capturing system. The breast displacement and the reduced percentage of controlled breast displacement (RBD) are proposed as the main parameters for evaluating the shock absorbing performance of sports bras. The naked breast displacement ranged from 1.01 to 4.37 cm. The breast displacement was the largest during stepping at the nipple. However, the RBD was larger at outer breast when wearing sports bras. The magnitude of shock absorption did not agree with the support levels claimed by the manufacturers. The encapsulation bras were more effective than compression bras in controlling breast displacement. The encapsulation bra EP-2 was the most effective shock absorber due to its higher content of polyamide, wider shoulder strap and higher neckline.